First report of Ochrobactrum anthropi isolated from bloodstream infection in Alexandria, Egypt - Amira ElBaradei; Nancy Ahmed; Sherine Shawky (Microbes and Infectious Diseases, 2022)
Background: Ochrobactrum anthropi ( O. anthropi) is a Gram-negative, nonfermenting bacillus, which has been recovered from clinical samples worldwide. However, it has never been reported from any clinical sample in Egypt. To the best of our knowledge, we report for the first time, the isolation of O. anthropi from bloodstream infection of a 75-year-old female patient. Ochrobactrum anthropi identification was performed using Vitek-2 system (BioMérieux, Marcy l’Etoile, France), and confirmed using 16S rRNA sequencing. The organism was further classified as O. anthropi subclade I, using recA sequence analysis. Susceptibility testing was carried out using broth microdilution method, and the isolate was found to be resistant to both ceftazidime and cefepime. Molecular investigation of genes conferring resistance to the third and fourth generation cephalosporins, showed that the isolate harbored blaOCH-6 gene, and that blaTEM, blaSHV and blaCTX-M were not present. This work highlights the first isolation of O. anthropi from bloodstream infection in Alexandria, Egypt.